2014
DOI: 10.1080/21641846.2014.881155
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and body mass index in the Fragile X premutation carrier

Abstract: Background: Recent evidence has shown that mitochondrial dysfunction may be significant in carriers of the Fragile X premutation. Purpose: The present study examined fatigue severity and body mass index (BMI) (two possible outcomes related to mitochondrial dysfunction) in premutation carriers with and without the Fragile X-associated Tremor Ataxia Syndrome (FXTAS) as compared to controls. Methods: Surveys to gather data on height and weight and fatigue impact (Fatigue Severity Scale) were sent out to previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Chronic fatigue is a common symptom of premutation carriers with and without FXTAS and it has a significant effect on their daily lives ( 85 , 86 ). It is likely associated with the mitochondrial dysfunction described previously in premutation carriers; previous studies have linked chronic fatigue in carriers with the severity of mitochondrial dysfunction ( 32 , 33 ).…”
Section: Chronic Fatiguementioning
confidence: 99%
See 2 more Smart Citations
“…Chronic fatigue is a common symptom of premutation carriers with and without FXTAS and it has a significant effect on their daily lives ( 85 , 86 ). It is likely associated with the mitochondrial dysfunction described previously in premutation carriers; previous studies have linked chronic fatigue in carriers with the severity of mitochondrial dysfunction ( 32 , 33 ).…”
Section: Chronic Fatiguementioning
confidence: 99%
“…Increased BMI is also thought to be indirectly related to fatigue because of its relation to sleep apnea, diabetes and coronary artery disease. Summers et al ( 85 ) reported that premutation carriers with FXTAS are more affected by fatigue than the individuals with premutation without FXTAS and the control group. Premutation carriers without FXTAS show an intermediate level between FXTAS patients and controls.…”
Section: Chronic Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Iron dysregulation has been linked to a series of neurodegenerative disease, including Parkinson and Alzheimer diseases, amyotrophic lateral sclerosis, restless legs syndrome, and prion diseases [21]. Indeed, Parkinsonism and dementia are common in those with FXTAS [7,22], and restless legs syndrome is more common in those with the premutation compared to controls [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Additional medical problems that are common in carriers, particularly aging carriers with neurological problems or FXTAS, include hypothyroidism (50% of females) [ 85 ], fibromyalgia (43% of females) [ 85 ], sleep apnea [ 86 ], migraine headaches [ 87 ], Restless Legs syndrome [ 88 ], fatigue [ 89 ] and hypertension [ 90 ]. Regular screening for hypothyroidism, hypertension, migraines, and sleep apnea are recommended because these problems also require treatment and can interfere with brain function if untreated.…”
Section: Expanding the Premutation Clinical Picturementioning
confidence: 99%